Thirty-five-year trends in cardiovascular risk factors in Finland - Vartiainen, Erkki; Laatikainen, Tiina; Peltonen, Markku; Juolevi, Anne; Männistö, Satu; Sundvall, Jouko; Jousilahti, Pekka; Salomaa, Veikko; Valsta, Liisa; Puska, Pekka (International Journal of Epidemiology, 2010)
Background In the late 1960s, coronary heart disease (CHD) mortality among Finnish men was the highest in the world. From 1972 to 2007, risk factor surveys have been carried out to monitor risk factor trends and assess their contribution to declining mortality in Finland. Methods The first risk factor survey was carried out in the North Karelia and Kuopio provinces in 1972 as the basis for the evaluation of the North Karelia Project. Since then, up to five geographical areas have been included in the surveys. The target population has been persons aged 25–74 years, except in the first two surveys where the sample was drawn from a population aged 30–59 years. Risk factor contribution on mortality change was assessed by a logistic regression model. Results A remarkable decline in serum cholesterol levels was observed between 1972 and 2007. Blood pressure declined among both men and women until 2002 but levelled off during the last 5 years. Prevalence of smoking decreased among men. Among women, smoking increased throughout the survey years until 2002 but did not increase between 2002 and 2007. Body mass index (BMI) has continuously increased among men. Among women, BMI decreased until 1982, but since then an increasing trend has been observed. Risk factor changes explained a 60% reduction in coronary mortality in middle-aged men while the observed reduction was 80%. Conclusions The 80% decline in coronary mortality in Finland mainly reflects a great reduction of the risk factor levels; these in turn have been associated with long-term comprehensive chronic disease prevention and health promotion interventions.